Exploring the catalytic capabilities of NiS@MoS2 2D for the production of Green Hydrogen - Gowhar A. Naikoo; Mustri Bano; Mohd M. Ayyub; Israr U. Hassan; Tawfik A. Saleh (Nano Trends)
This study aims to delve into the catalytic capabilities of MoS2 and NiS deposited MoS2 (NiS@MoS2) 2D material explored via a facile hydrothermal process for HER (hydrogen evolution reaction). The shape and structural properties of these 2D materials were evaluated by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), energy-dispersive X-ray (EDX) spectroscopy, scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), and Raman techniques. The XRD study of the NiS@MoS2 sample highlighted notable shifts in the peaks as well as the emergence of distinctive additional peaks, indicative of structural changes due to the deposition of NiS. Electrochemical impedance spectroscopy (EIS) and Cyclic voltammetry (CV) were applied to assess their HER. The decrease in Tafel slope in NiS@MoS2 validated the increase in electrocatalytic activity, which was further corroborated by a decrease in charge transfer resistance (Rct). The onset potential (−0.14 V, vs Ag/AgCl) and the overpotential (η@10) (−0.30 V) of NiS@MoS2 have exposed the enhanced HER activity of NiS decorated MoS2 materials. Conclusively, this research work underscores the significant potential of NiS@MoS2 nanostructures in driving efficient and sustainable green hydrogen production, making a pivotal step forward in energy research.